Toxicity of clomazone and its formulations to zebrafish embryos (Danio rerio) - Stevanovic, Marija; Gasic, Slavica; Pipal, Marek; Blahova, Lucie; Brkic, Dragica; Neskovic, Nesko; Hilscherova, Klara (Aquatic toxicology (Amsterdam, Netherlands), 2017)
Herbicides are the most widely used group of pesticides but after reaching water bodies they are able to cause adverse effects on non-target organisms. Different formulations using the same active ingredient are frequently available, which raises the issue of potential influence of different formulation types on herbicide toxicity. The present study evaluated the toxicity and teratogenic effects of the active ingredient clomazone and its two formulations (Rampa® EC and GAT Cenit 36 CS, both containing 360g a.i./l of clomazone) on zebrafish embryos. The crucial difference between the two formulation types is the way of active substance release. This investigation is the first report on zebrafish embryotoxicity of both clomazone and its formulations. The technical active ingredient and formulations caused mortality and diverse teratogenic effects, showing different levels of toxicity. The LC50 values for the technical ingredient, Rampa® EC and GAT Cenit 36 CS were 61.4, 9.6 and 92.5mg a.i./l, respectively. Spontaneous movements in 22 hpf embryos decreased under exposure to both the technical ingredient and formulations. A significant number of underdeveloped embryos was detected after exposure to clomazone and Rampa® EC, while no underdevelopment was noted in embryos exposed to GAT Cenit 36 CS. Exposure to the technical ingredient and formulations led also to a series of morphological changes and interfered with the growth of zebrafish embryos. The EC50 based on detection of edemas, spine and tail tip deformations and gas bladder absence (120hpf) was 12.1, 10.1 and 24.1mg/l for technical clomazone, Rampa® EC and GAT Cenit 36 CS, while teratogenicity index (TI) based on LC50/EC50 ratio was 5.1, 1 and 3.8, respectively. The data in this study showed that the emulsifiable concentrate formulation (Rampa® EC) caused statistically significantly higher toxicity, and the aqueous capsule suspension (GAT Cenit 36 CS) lower toxicity than technical clomazone. It indicates that different formulations with the same active ingredient may have different environmental impacts, which is why risk assessment based only on active ingredient toxicity might not be sufficient in terms of preventing formulation effects on the environment.
Keywords: Clomazone; dánio pruhované; Formulations; Animals; Embryo, Nonmammalian; Herbicides; oxazolidinony; embryo nesavčí; herbicidy; Embryotoxicity; isoxazoly; chemické látky znečišťující vodu; Isoxazoles; Zebrafish; Embryo; Water Pollutants, Chemical; Oxazolidinones; zvířata